Late Miocene (Messinian) Stylasteridae (Cnidaria, Hydrozoa) from Carboneras, southeastern Spain. (March 2020) - Cairns, Stephen D.
Abstract: Fifteen species of stylasterids from the late Miocene (Messinian) are reported from the Carboneras region of southeastern Spain. Eleven of these species are described as new: Lepidopora fistulosa, Pliobothrus striatus, Pliobothrus nielseni, Distichopora patula, Stylaster (Group A) digitiformis, Stylaster multicavus, Stylaster tuberosus, Conopora forticula, Conopora alloporoides, Crypthelia zibrowii, and Crypthelia ingens . The other four have been identified as species previously described from the Recent fauna. On the basis of bathymetric ranges of similar living stylasterids and other associated fauna, the paleodepth of this fauna is estimated to be from the upper bathyal zone (200–600 m). All fossil stylasterid records, worldwide, are reviewed, resulting in four new combinations and the transfer of one species to the Bryozoa. The species reported herein increase the known number of named fossil stylasterids from 24 to 32 species. UUID: http://zoobank.org/e9140758-847c-44cb-8223-302cc0a0a14d